2009
DOI: 10.1002/ajmg.a.32761
|View full text |Cite
|
Sign up to set email alerts
|

International Research Symposium on Ankyloblepharon‐Ectodermal Defects‐Cleft Lip/Palate (AEC) Syndrome

Abstract: Ankyloblepharon-Ectodermal Defects-Cleft Lip/Palate (AEC) Syndrome (Hay-Wells syndrome, MIM #106220) is a rare autosomal dominant ectodermal dysplasia syndrome. It is due to mutations in the p63 gene, known to be a regulatory gene with many downstream gene targets. TP63 is important in the differentiation and proliferation of the epidermis, as well as many other processes including limb and facial development. It is also known that mutations in p63 lead to skin erosions. These erosions, especially on the scalp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 27 publications
0
30
0
1
Order By: Relevance
“…This is caused, in part, by the lack of availability of skin samples for this rare disorder. We obtained skin biopsies from AEC patients, thus allowing us to interrogate abnormal expression of genes and proteins associated with skin integrity (Fete et al, 2009; Koster et al, 2009; Beaudry et al, 2009). Consistent with reports using smaller sample sets, our analysis of AEC patient skin revealed the presence of suprabasal proliferation, impaired terminal differentiation, and abnormal deposition of basement membrane components (Koster et al, 2009; Marinari et al, 2009; Clements et al, 2012; Browne et al, 2011; McGrath et al, 2001).…”
Section: Deregulation Of Desmosomal Proteins and Genes In Aecmentioning
confidence: 99%
“…This is caused, in part, by the lack of availability of skin samples for this rare disorder. We obtained skin biopsies from AEC patients, thus allowing us to interrogate abnormal expression of genes and proteins associated with skin integrity (Fete et al, 2009; Koster et al, 2009; Beaudry et al, 2009). Consistent with reports using smaller sample sets, our analysis of AEC patient skin revealed the presence of suprabasal proliferation, impaired terminal differentiation, and abnormal deposition of basement membrane components (Koster et al, 2009; Marinari et al, 2009; Clements et al, 2012; Browne et al, 2011; McGrath et al, 2001).…”
Section: Deregulation Of Desmosomal Proteins and Genes In Aecmentioning
confidence: 99%
“…They are mainly located on the scalp and may extend to the neck, shoulders, back and buttocks. Palms and soles might be involved (18% in our series) . Complete wound healing varies from 2 months to 12 years.…”
Section: Discussionmentioning
confidence: 83%
“…Complete wound healing varies from 2 months to 12 years. Persistent and/or recurrent erosions on the scalp impact the daily life and might interfere with the laying of the hearing aid . The pathophysiological mechanisms of erosions and their healing remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggested that the dysregulation of the EDA‐NF‐κB signaling pathway resulted in abnormal skeletogenic neural crest cell differentiation, migration, and osteoclastic differentiation such that craniofacial abnormalities presented clinical signs in ED patients . Mutation of the p 63 gene also caused disorders in facial development because the transcription and expression of the p 63 gene played an essential role in epidermal differentiation and proliferation during embryogenesis . Additionally, other authors suggested that craniofacial features, such as reduced maxilla length and prognathism, retroclined nasal bone, short nose, and reduced facial height, also resulted from the absence of teeth .…”
Section: Discusionmentioning
confidence: 99%